Collaborative HRM, climate for cooperation, and employee intra-organizational social ties in high-technology firms in China: A cross-level analysis - Su, Zhongxing; Zhou, Mengfei; Li, Xiaobei; Yang, Yuxin; Shi, Wei (Frontiers in Psychology, 2023)
Individual social ties have been an important source of competitive advantages for high-tech firms in the knowledge economy. Based on the data collected from 363 knowledge employees working in 64 high-tech firms in China, we examine the cross-level relationships among collaborative HRM practices, climate for cooperation and employee intra-organizational social ties. The hierarchical linear model results show that organizational-level collaborative HRM practices have significant positive effects on the number and strength of individual-level intra-organizational social ties, and the climate for cooperation mediates these relationships.